Efektivitas Pemeriksaan Fisik Dan Edukasi Pada Premenopause Dan Lansia Dengan Tingkat Kecemasan Di Wilayah Puskesmas Cimarga - Syahriawati , Lisna; Idealistiana , Lia (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Changes that occur physically, psychologically and sexually cause women who are facing menopause to be anxious and worried. Excessive anxiety can have bad effects on the body. Methods: research with a cross sectional study approach, for the educational variable, the type of research used is quasi-experimental. The research design uses two group measurements (observations) with a Pretest Posttest design. Sampling used a minimum experimental research sample according to Gay and Diehl, namely 20 samples per group, a total of 40 people. The sampling technique used was purposive sampling Results & Conclusion: 1) The level of anxiety in premenopausal and elderly people after a physical examination of blood pressure is dominant at the level of mild anxiety with normal blood pressure physical examination results, namely 17 people (37.0%). 2) The level of anxiety in premenopausal and elderly people after a physical temperature examination, the level of mild anxiety with normal examination results was the highest, namely 20 people (43.5%). 3) The level of anxiety in premenopausal and elderly people after Hb examination mostly showed a mild level of anxiety with normal examination results, totaling 13 people (28%). 4) The level of anxiety in premenopausal and elderly people after the GDS physical examination was carried out showed that mild levels of anxiety dominated the normal GDS examination results with a figure of 14 people (30.4%). 5) The mean value of the pretest results for the intervention group was 2.74, the mean value of the posttest results was 1.91. The results of the Wilcoxon test were significant, p-value 0.001 <0.05, which means there was a difference in pretest and posttest anxiety levels in the intervention group. 6) The results of the Mann Whitney test are significant p-value .032 < 0.05. This means that there is an influence of physical examination and education on changes in anxiety levels in premenopausal and elderly people.